Multigenerational Effects of an Environmentally Relevant Phthalate Mixture on Reproductive Parameters and Ovarian miRNA Expression in Female Rats. (28th June 2022) - Gonsioroski, Andressa V; Aquino, Ariana M; Alonso-Costa, Luiz G; Barbisan, Luis F; Scarano, Wellerson R; Flaws, Jodi A
Abstract: Phthalates are endocrine-disrupting chemicals used in many consumer products. Our laboratory previously developed an environmentally relevant phthalate mixture consisting of 6 phthalates and found that it disrupted female fertility in mice. However, it was unknown if maternal exposure to the mixture affects reproductive parameters and ovarian post-transcription in the F1 and F2 generation of female rats. Thus, we tested the hypothesis that maternal exposure to the phthalate mixture affects folliculogenesis, steroidogenesis, and ovarian microRNA (miRNA) in the F1 and F2 generations of female rats. Pregnant female rats were divided into 4 groups and orally dosed daily from gestational day 10 to postnatal day 21 with corn oil (control group), 20 μg/kg/day, 200 μg/kg/day, or 200 mg/kg/day of the phthalate mixture. Maternal exposure to the phthalate mixture impaired folliculogenesis in the F1 and F2 generations of female rats and affected steroidogenesis in the F1 generation of female rats compared to control. Further, the phthalate mixture altered ovarian expression of some genes related to the cell cycle and steroidogenesis compared to control in the F1 and F2 generations of female rats. The mixture also increased ovarian expression of rno-mir-184 that is involved with the oocyte maturation process. Collectively, our data show that maternal exposure to the phthalate mixture affects folliculogenesis and steroidogenesis in the F1 and F2 generations of female rats and alters ovarian miRNA expression in the F1 generation of female rats.